Plantas Amazonicas de uso medicinal: diagnostico de un sector economico con un potencial de realizacion - Nalvarte A.W.; Jong, W. de; Domínguez, G. (CIFOR and Universidad Nacional Agraria La Molina, Lima, Peru, 1999)
This is a report on the trade of medicinal plants in Peru, the manufacturing industry that relies on these plants, the research on promotion of their use, and on the legal instruments that govern their use, trade and transformation. In Peru medicinal plants have been used for centuries. However, since 1994 the trade of these plants has boomed. Local collectors gather the fresh material which they trade in markets in the principal cities throughout Peru. They engage in medicinal plant trade as an activity complementary to their agricultural activities. The larger commercial collections have occurred since 1994 to meet the international demand for Uncaria tomentosa and U. guianensis Collection is still the dominant form of procurement of medicinal plants in Peru. It is the initial step of a production chain of activities, including pharmaceutical companies that prepare a number of derivatives traded as food additives nationally and to some extent internationally. These companies are mostly located in Lima and they buy their raw material from intermediaries with whom they have mostly informal agreements. In some cases these agreements are with members of indigenous villages. Such companies have inadequate market information systems that could improve their planning. The USA is the largest buyer of medicinal plants from Peru. These plants are, after processing, sold to other destinations. Peru has so far had little access to international markets because of limited dominance of the required technology and high processing costs. The added value of the export of medicinal plants is therefore quite low. Control of this forest resource is insufficient. It is extracted from non-managed forests from areas of unknown extension. Current legislation does not guarantee the sustainable extraction. The state charges fees when extraction occurs, but has little opportunity to control actual levels and it does not engage in any kind of on the ground control, management, or restoration of natural populations. There is insufficient knowledge for the production of medicines that can meet strict standards imposed by law. Consequently many companies are considering abandoning the manufacture of medicinal plant derivatives. There is a need for adequate research, legal instruments and policy to enable greater benefits to the Peruvian economy and people from this forest resource.